Sarcopenia, in-hospital mortality and prolonged hospital stay in elderly subjects admitted to a Peruvian reference hospital - Ramos-Ramirez, Keyla E. (2020)
Objective: to determine whether sarcopenia is an associated factor to in-hospital mortality and prolonged hospital stay (PHS) in elderly subjects admitted to Hipolito Unanue National Hospital (HUNH) between December 2019 and March 2020. Materials and methods: this is an observational prospective cohort study performed in elderly subjects admitted to the Medicine Service in HUNH. Crude and multivariate analysis were performed using Poisson regression, aiming to determine a relationship between sarcopenia and in-hospital mortality and PHS by relative risk (RR). Results: nearly half of all patients (49.4%) in the study had sarcopenia, 12.3% died, and 32.5% had PHS. The crude analysis showed an association between sarcopenia and in-hospital mortality (RR: 4.69, 95% CI: 1.62–13.10, p=0.004); nonetheless, when an adjusted analysis was performed, this significance value got lost (p=0.097). No significant association was found between sarcopenia and PHS (p=0.673). Conclusion: sarcopenia is a condition affecting a large proportion of hospitalized elderly subjects, and it is associated to a higher risk of dying during hospitalization. There is no association between sarcopenia and PHS.